Hamka Sebagai Sejarawan: Kajian Metodologi Sejarah terhadap Karya Hamka - Rahmi Nur Fitri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Hamka was a contemporary Indonesian Islamic figure who was involved in many fields. He wrote hundreds of books on various topics of study, philosophy, interpretation, history, customs and culture, literature, and others. When mentioning the name Hamka, then he was an ulama, while his roles in other fields are a little blurred. One of them is a depiction of the figure of Hamka as a historian. Some researchers recognize and acknowledge it as part of a historical researcher, some even study his historical philosophy, while for others give the view that he is not a historian. There are several characteristics and types of historians themselves, including professional historians, historians of other fields, and amateur historians or so-called community historians. The purpose of this paper is to uncover the methods employed by Hamka in writing his historical-themed works by looking at the intellectual socio-historical life. Through this study, it can be concluded that Hamka is included in the class of community historians because there is no formal academic history in his study. However, the various steps he went through in the writing process and his teaching experience are proof that Hamka is a historian.